Time-to-Contact Estimation Modulated by Implied Friction. (February 2014) - Yamada, Yuki; Sasaki, Kyoshiro; Miura, Kayo
The present study demonstrated that friction cues for target motion affect time-to-contact (TTC) estimation. A circular target moved in a linear path with a constant velocity and was gradually occluded by a static rectangle. The target moved with forward and backward spins or without spin. Observers were asked to respond at the time when the moving target appeared to pass the occluder. The results showed that TTC was significantly longer in the backward spin condition than in the forward and without-spin conditions. Moreover, similar results were obtained when a sound was used to imply friction. Our findings indicate that the observer's experiential knowledge of motion coupled with friction intuitively modulated their TTC estimation.